Dam inactivation in Neisseria meningitidis: prevalence among diverse hyperinvasive lineages (BioMed Central, 2004)

(untitled)
Background: DNA adenine methyltransferase (Dam) activity is absent in many, but not all, disease isolates of Neisseria meningitidis, as a consequence of the insertion of a restriction endonucleaseencoding gene, the 'dam replacing gene' (drg) at the dam locus. Here, we report the results of a survey to assess the prevalence of drg in a globally representative panel of disease-associated meningococci. Results: Of the known meningococcal hyper-invasive lineages investigated, drg was absent in all representatives of the ST-8 and ST-11 clonal complexes tested, but uniformly present in the representatives of the other hyper-invasive lineages present in the isolate collection (the ST-1, ST- 4, ST-5, ST-32 and ST-41/44 clonal complexes). The patterns of sequence diversity observed in drg were consistent with acquisition of this gene from a source organism with a different G+C content, at some time prior to the emergence of present-day meningococcal clonal complexes, followed by spread through the meningococcal population by horizontal genetic exchange. During this spread a number of alleles have arisen by mutation and intragenic recombination. Conclusion: These findings are consistent with the idea that possession of the drg gene may contribute to the divergence observed among meningococcal clonal complexes, but does not have a direct mechanistic involvement in virulence.